Analysis of humanistic-based Islamic education curriculum in addressing moral degradation - Muhammad Yoggi Aqsal Darmawan; Iqbal Ahsanul Aula (Himpunan Pengembang Kurikulum Indonesia, 2025)
The humanistic curriculum provides a solution to educate students to find their identity. In a humanistic curriculum, students are taught to express their human potential as free individuals. However, the freedom granted to students in undergoing the academic process can become a problem if students lack the desire or ability to understand their potential, leading to a loss of direction in their learning process, which can eventually result in moral degradation. This study aims to analyze the development of a humanistic-based Islamic Education curriculum in dealing with the degradation of moral values that occurs in middle-class students. The method used is qualitative with in-depth interviews and reinforced with an in-depth literature study approach, involving analysis of books, journals, and government policy documents. The results of the study indicate that the humanistic curriculum results in a lack of teacher authority in providing firm direction against violations of norms, which has the potential to cause moral degradation of students. Therefore, a policy update is needed that integrates the balance between teachers and students. This study recommends a review of the policy to be more in line with national education goals and practical needs in the field. Abstrak Kurikulum humanistik memberikan solusi untuk mendidik siswa menemukan jati dirinya. Pada kurikulum humanistik, siswa diajarkan untuk mengekspresikan potensi sifat kemanusiaannya sebagai individu yang bebas. Namun, kebebasan yang diberikan kepada siswa dalam menjalani proses akademis dapat menjadi masalah jika siswa tidak memiliki keinginan atau kemampuan untuk memahami potensi diri mereka, sehingga mereka mungkin kehilangan arah dalam proses belajar yang akan menggiring pada degradasi moral. Penelitian ini bertujuan menganalisis pengembangan kurikulum PAI berbasis humanistik dalam menghadapi degradasi nilai moral yang terjadi pada siswa kelas menengah. Metode yang digunakan adalah kualitatif dengan wawancara mendalam dan diperkuat dengan pendekatan studi literatur yang mendalam, melibatkan analisis dari buku, jurnal, dan dokumen kebijakan pemerintah. Hasil penelitian menunjukkan bahwa kurikulum humanistik menimbulkan kurangnya otoritas guru dalam memberikan arahan tegas terhadap pelanggaran norma, yang berpotensi terjadinya degradasi moral siswa. Oleh karena itu, diperlukan pembaruan kebijakan yang mengintegrasikan keseimbangan antara guru dan siswa. Penelitian ini merekomendasikan peninjauan kembali kebijakan agar lebih sesuai dengan tujuan pendidikan nasional dan kebutuhan praktis di lapangan. Kata Kunci: degradasi moral; pendidikan agama Islam; kebijakan pendidikan Islam